Coping with parental migration: A qualitative study on the social adaptation of left-behind children in Henan, China - Lei, Daxia; Singh, Paramjit Singh Jamir; Azman, Azlinda (International Journal of Asian Social Science, 2024)
This study explores the key challenges faced by left-behind children and examines their coping strategies, with the aim of proposing methods to enhance their social adaptation. Employing qualitative in-depth interviews, the research gathers data from left-behind children in rural areas, identifying a spectrum of coping strategies related to parental migration and evaluating their effects on social adaptation. These strategies include acceptance, environmental adaptation, the use of social media platforms like short-video apps, seeking social support, engaging in recreational activities, emotional self-regulation, and maintaining a positive outlook. The study offers a fresh perspective and framework for the social adaptation service system and advocates for the development of a social work model tailored to rural left-behind children.